Factors for true chamomile processing in the tea industry - Aliaga-Paredes, Elio-Luis (2018)
This article summarizes the main factors for the production of true chamomile tea bags: market, raw material, industry, regulations and production process. In addition, other factors are considered in the production process according to the reality of life in Peru: equipment, energy evaluation, health standards, technical specifications of the product, maintenance system, labor and materials cost, required areas, and occupational health and safety.